Identifikasi Potensi dan Pemanfaatan Tumbuhan Obat di Hutan Produksi Kecamatan Sinoa Kabupaten Bantaeng Sulawesi Selatan - Husnah Latifah; Yusran Jusuf; Samuel A. Paembonan; H Hasanuddin; S Sultan (Fapetrik-UMPAR, 2020)
The purpose of this study was to determine the potential and benefits of medicinal plants found in production forests in Sinoa District, Bantaeng Regency. The type of data collected was quantitative and qualitative data, including types and quantities of medicinal plants, local names, parts of plants used, and types of diseases that can be treated with these plants. Vegetation analysis results showed that the diversity of medicinal plants as many as 13 species from 10 families. Vegetation which has the greatest potential at the level of the tree namely Pinus (Pinus mercusii) with a potential of 194, at the pole level was Avocado (Persea gratissima) with a potential of 100, at the sapling level namely Coffee (Coffea arabica) with a potential of 640, and at the seedling level ie Bandotan (Ageratum conyzoides) with the greatest potential is 17500. Plant parts that utilized were leaves, roots, fruits, seeds, sap, and bark. All of these parts used to treat diseases such as shortness of breath, headache, toothache, cough, diarrhea, fever, malaria, high blood pressure, diabetes, suppurating ulcers, beriberi, immune system, festering skin inflammation, and increasing brain intelligence. Besides that it can treat kidney stones, wounds, sore throat, eye medication, dry the wound, neutralize the poison boils, canker sores, bruises, swelling, and sprains.